2020
DOI: 10.1002/da.22993
|View full text |Cite
|
Sign up to set email alerts
|

Courses of suicidal ideation among military veterans in residential treatment for posttraumatic stress disorder

Abstract: Background Suicidal thoughts are common among veterans with posttraumatic stress disorder (PTSD). The aim of this study was to examine the prevalence and correlates of four courses of suicidal (SI) among veterans receiving residential PTSD treatment. Methods A total of 1,807 veterans receiving residential PTSD treatment at Department of Veterans Affairs medical facilities who completed self‐report measures at admission and discharge were included. Results The prevalence of SI courses were No SI (33.6%), Remitt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 52 publications
2
3
0
Order By: Relevance
“…This is consistent with other studies of veteran samples that have found SI to significantly decrease over the course of EBPs for PTSD (e.g., Stayton et al, 2019). Specifically, this is consistent with findings from a residential PTSD treatment program, which found that changes in PTSD symptomatology did not differ for those with differing severity levels of SI at pretreatment (Smith et al, 2020). The present study reflects a similar extension of these findings to an outpatient sample of veterans in PTSD treatment.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…This is consistent with other studies of veteran samples that have found SI to significantly decrease over the course of EBPs for PTSD (e.g., Stayton et al, 2019). Specifically, this is consistent with findings from a residential PTSD treatment program, which found that changes in PTSD symptomatology did not differ for those with differing severity levels of SI at pretreatment (Smith et al, 2020). The present study reflects a similar extension of these findings to an outpatient sample of veterans in PTSD treatment.…”
Section: Discussionsupporting
confidence: 92%
“…A recent study examined outpatient CPT and PE treatment together and found that SI significantly decreased over the course of these EBPs for PTSD and that PTSD symptom clusters were associated with changes in SI (Horwitz et al, 2019). Finally, similar results were found in a sample of veterans in residential treatment engaged in either CPT or PE, such that SI decreased over the course of treatment and PTSD symptoms were significantly associated with these decreases in SI (Smith et al, 2020). Overall, the literature shows that EBPs for PTSD result in significant reductions in suicidal ideation over the course of treatment in both outpatient and residential treatment settings.…”
Section: Ptsd and Suicidal Ideationsupporting
confidence: 64%
See 2 more Smart Citations
“…There is limited research on evidence-based treatment for PTSD and its impact on suicidal thoughts and behaviors. A national study examined the prevalence and correlates of SI in a national sample of veterans in residential PTSD treatment and found an absence of SI among the majority of participants, although 43% still endorsed some level of suicidal ideation (Smith et al, 2020). Other studies found that treatment of PTSD in veterans could be associated with reductions in suicidal ideation (e.g., Stayton et al, 2019) in residential treatment.…”
Section: Ptsd Treatment and Its Impact On Suicidal Thoughts And Behav...mentioning
confidence: 99%